Meta‐omics reveal microbial assortments and key enzymes in bean sauce mash, a traditional fermented soybean product. (27th August 2019) - Xie, Mengxi; An, Feiyu; Wu, Junrui; Liu, Yiming; Shi, Haishu; Wu, Rina
Abstract: BACKGROUND: Dajiang is fermented based on the metabolism of microbial communities in bean sauce mash, a traditional fermented soybean product in China. The current study first investigated the metaproteome of bean sauce mash. This was followed by an analysis of its biological functions and its microbial community to reveal information about strains and about the expressed proteins to better understand the roles of the microbiota in bean sauce mash. RESULTS: The metaproteomic results demonstrated that a total of 1415 microbial protein clusters were expressed mainly by members of the Penicillium and Rhizopus genera and were classified into 100 cellular components, 238 biological processes, and 220 molecular function categories by gene ontology (GO) annotation. Enzymes associated with glycolysis metabolic pathways were also identified. These can provide the energy required for microbial fermentation. Illumina MiSeq sequencing technology results showed that the microorganism communities of bean sauce mash exhibited a high level of diversity. Microbiological analysis demonstrated that the Penicillium, Mucor, Fusarium, Aspergillus, and Rhizopus fungi, and Lactobacillus, Enterococcus, Fructobacillus, Staphylococcus, Carnobacterium genera were predominant 22 samples. CONCLUSION: The profiles and insights in the current study are important for research on bean sauce mash and related products in terms of their food microbial ecology. The information obtained from this study will help the development of stable sufu starter cultures with unique sensory qualities. © 2019 Society of Chemical Industry